L’Héritage colonial de la Casbah d’Alger. Tentative d’effacement ou réelle réappropriation ? - Asma Hadjilah (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article focuses on the colonial urban and architectural heritage of the Casbah of Algiers, as well as initiatives undertaken for its preservation and enhancement following independence. It specifically addresses the interventions carried out within the new urban dynamic experienced by the Algerian capital since the 2000s. The aim is to shed light on design approaches and attitudes, whether they concern public buildings or ordinary architecture. It first considers the means by which these buildings benefit from legal protection today, followed by the impact of comprehensive development and urban planning schemes. Finally, it seeks to identify resignification strategies adopted in order to ensure the successful reappropriation of this heritage.